Fundamentals of computer systems architecture - Gavrylenko, Svitlana; Khatsko, N. (National Technical University "Kharkiv Polytechnic Institute", 2019)
In the study guide "Fundamentals of computer systems architecture" the questions of presentation of information in different systems of calculation, execution of logical and arithmetic operations are considered. Each chapter provides the necessary theoretical information, examples of presentation of information and examples of execution of arithmetic and logical operations, given tasks for self-execution and control questions. For the students of specialties 121 – “Software Engineering” and 123 – “Computer Engineering”.
Keywords: number systems; computer calculations; typical computer registers; bitwise operations; logical operations; adding binary numbers; floating-point representation; commonly rules